Contemporary Education:: Reflections on the use of multiliteracies in the classroom context in the Amazonian interior - Queiroz, Jacson da Silva; Tanzi Neto, Adolfo (The ESPecialist, 2024)
This article aims to reflect on the contributions of multiliteracies in the classroom context in the interior of the Amazon. Thinking about multiliteracies for the educational context needs to consider social and cultural diversity and multimodality in the construction of meanings. From this perspective, we dialogue with Rojo (2012), Cope and Kalantzis (2015) and Kalantzis, Cope and Petrilson (2020) when they present that we need to redefine reading, writing and practices in the construction of meaning in contemporary communication environments. The methodology is based on bibliographical research, which is expected to contribute to providing teaching-learning actions articulated with multiliteracies in the Amazonian classroom.